Implementasi Praktikum Berbasis Diagram Vee Untuk Memunculkan Kemampuan Metakognitif Dan Penguasaan Konsep Siswa - Selly Nur Daniyanti; Anna Fitri Hindriana; Sri Redjeki (Edubiologica: Jurnal Penelitian Ilmu dan Pendidikan Biologi, 2018)
The aim of the research is to determine the implementation of lab activities based Vee diagram to bring out students metacognitive skill and increasing students' learning achievement to the excretory system. Quasi-experimental research with nonequivalent control group design was conducted to the classes. Lab activities based Vee diagram was implemented to the experimental class and lab activities based guided inquiry was implemented to the control class. The sample was determined by purposive sampling technique. Data of the research was obtained from student’ worksheet that applying metacognitive strategies and the result of  pre test and post test. Metacognitive skills of experimental class is higher than the control class. Based on analysis, metacognitive skills of experimental class was 75.0 and metacognitive skill of control class was 67.8. Learning achievement of experimental class is higher than control class. The results of the test showed an increasing (N gain) of learning achievement experimental class was 0.53 and control class was 0.41. T test showed t count > t table, which means that there are significant differences between pre-test and post test. Correlation test results showed the corellation between metacognitive skills and learning achievement is very high at 96.7%Keywords: Vee diagram; Guided inquiry; Metacognitive skill; Learning achievement